Peran Strategi Orientasi Wirausaha, Orientasi Pasar Dan Pengaruhnya Terhadap Kinerja Usaha Pada UMKM - Achmad Daengs GS; Rina Dewi; Sugiharto Sugiharto; Bambang Karnain; Enny Istanti (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
The contribution of MSMEs to economic growth means that MSME performance needs to be improved. In this case, there are many factors that must be considered in improving the performance of MSMEs, such as entrepreneurial orientation and market orientation, so this research was conducted with the aim of analyzing the significant influence of entrepreneurial orientation and market orientation on business performance in MSMEs. This research was conducted using a quantitative approach. The samples taken were 50 MSME business people assisted by the Surabaya City Trade Office. Data collection in this research was carried out by distributing questionnaires. The data analysis technique used in this research is multiple linear regression analysis. The results of this research show that entrepreneurial orientation and market orientation have a significant influence, both partially and simultaneously, on business performance in MSMEs.